Absurdism in Atirikta Yatra by K. S. Yatri and The American Dream by Edward Albee - Subedi, Tika Data (JMC Research Journal, 2018)
The purpose of this work is to study Edward Albee and K. S. Yatri’s approach regarding the status of respective societies of America and Nepal with absurd drama following their agenda. K. S. Yatri and Edward Albee seemed to be influenced by the absurdist mode of drama which concerns much about the modern existence of social human beings. Albee follows absurdist traces in the dramatization of uncertainty, alienation and the question of freedom in The American Dream. His characters do not have fixed identities, and they suffer from their individual problems. The notion of the characters and their activities too are uncertain. In the same way, the ambiguity of existence, whether the characters really are or not, is a problem for the characters in Atirikta Yatra. The characters are based on illusions, and the line between the reality and fantasy is missing. Alienation of the human being from the self and the other is existential theme that K. S. Yatri deals with in Atirikta Yatra. Alienation in the play is caused by the lack of communication, and as a result, the isolated self is entrapped in Yatri’s characters due to their own condition. Freedom becomes a confusing question in his works as it makes the characters anxious while choosing one option among various others on their own, and it renders the characters responsible for their free choices. Though, two texts belong to divergent space however both show how absurdism has affected individuals and society everywhere at present.